Differences in the acute phase responses of serum amyloid P-component (SAP) and C3 to injections of casein or bovine serum albumin in amyloid-susceptible and -resistant mouse strains. - Baltz, M L (1980)
In CBA/Ca and C57Bl/Cbi mice, which are susceptible to casein-induced amyloidosis, daily injections of casein caused a marked rise in the level of circulating serum amyloid P-component (SAP), which was sustained while injections continued. In contrast, mice given bovine serum albumin (BSA) injections showed only a small, transient increase in SAP levels. A/J mice, which are relatively resistant to casein-induced amyloidosis, also developed high SAP levels initially, but the increase was not maintained despite continued administration of casein. A/J mice receiving BSA had a slowly progressive rise in SAP which reached the same level as in the casein-treated animals. Administration of colchicine, which prevents casein-induced amyloidosis, suppressed the SAP response to casein in CBA mice. The serum level of the C3 component of complement, which is not an amyloid protein but is an acute phase reactant, also increased following casein injection. The rise in C3 was, however, proportionately less than that of SAP, was less sustained and was scarcely affected by colchicine. The present results therefore demonstrate different patterns in the acute phase response of different proteins in different mouse strains, and suggest that there may be a relationship between sustained high levels of SAP and the deposition of amyloid.